California's carbon market and energy prices: a wavelet analysis - Aguiar-Conraria, Luís (2018)
Carbon price is a key variable in management and risk decisions in activities related to the burning of fossil fuels. Different major players in this market, such as polluters, regulators and financial actors, have different time horizons. We use innovative multivariate wavelet analysis tools, including partial wavelet coherence and partial wavelet gain, to study the link between carbon prices and final energy prices in the time and frequency dimensions in California's carbon market, officially known as the California cap-and-trade programme. We find that gasoline prices lead an anti-phase relation with carbon prices. This result is very stable at lower frequencies (close to 1-year period cycles), and it is also present before mid-2015 in the 20-34 weeks frequency band. Regarding electricity, we find that at about a 1-year period, a rise in carbon prices is reflected in higher electricity prices. We conclude that the first 5 years of compliance of the California cap-and-trade programme show that emissions trading is a significant measure for climate change mitigation, with visible rising carbon prices. The quantitative financial analytics we present supports the recent decision to extend the current market to 2030 without the need for complementary carbon pricing schemes.This article is part of the theme issue 'Redundancy rules: the continuous wavelet transform comes of age'.